1980
DOI: 10.3758/bf03334494
|View full text |Cite
|
Sign up to set email alerts
|

Naming and categorization of tilted alphanumeric characters do not require mental rotation

Abstract: Single letters and numbers were shown at different angular orientations in the frontal plane, in both forward and backward (mirror-image) versions. In three separate conditions, subjects were required to discriminate the stimuli on the basis of version, category (letter, number, and name (G, 2, etc.). There was a pronounced effect of orientation on version judgments but none at all on category and name judgments, indicating that the identification of a tilted character requires neither the assignment of a cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
78
2

Year Published

1988
1988
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(88 citation statements)
references
References 9 publications
8
78
2
Order By: Relevance
“…These RT functions have been extensively replicated in parity-judgment tasks involving the discrimination of not only mirror-imaged characters, but also of left and right hands (Cooper & Shepard, 1975) of the mirror-image polygons (Ely, 1982), and of left-and right-facing naturalistic objects (Jolicoeur, 1985). Further, these RT functions are unique to parity judgment tasks: to our knowledge the only comparable phenomenon is the increased RTs obtained when subjects are required to identify rotated characters (Corballis, Zbrodoff, Shetzer, & Butler, 1978;White, 1980) or naturalistic objects (Jolicoeur, 1985). However, these tasks typically produce shallower RT slopes and a "dip" at 180 • , and it is debatable whether mental rotation is actually involved (see Jolicoeur, 1990;Murray, 1997) for more detailed treatments of this issue).…”
Section: Introductionmentioning
confidence: 69%
“…These RT functions have been extensively replicated in parity-judgment tasks involving the discrimination of not only mirror-imaged characters, but also of left and right hands (Cooper & Shepard, 1975) of the mirror-image polygons (Ely, 1982), and of left-and right-facing naturalistic objects (Jolicoeur, 1985). Further, these RT functions are unique to parity judgment tasks: to our knowledge the only comparable phenomenon is the increased RTs obtained when subjects are required to identify rotated characters (Corballis, Zbrodoff, Shetzer, & Butler, 1978;White, 1980) or naturalistic objects (Jolicoeur, 1985). However, these tasks typically produce shallower RT slopes and a "dip" at 180 • , and it is debatable whether mental rotation is actually involved (see Jolicoeur, 1990;Murray, 1997) for more detailed treatments of this issue).…”
Section: Introductionmentioning
confidence: 69%
“…A similar problem may inhere in White's (1980) experiment, where the presentation of a correct information cue for either identity or category may have allowed subjects to prepare for the task by looking for a diagnostic orientation-free feature (or by activating one or more orientationspecific representations based on the cue). In contrast, the presentation of a cue for handedness would not have allowed subjects to prepare for the handedness judgment, since handedness information does not in general allow any concrete feature or shape representation to be activated beforehand.…”
Section: Evidence Interpreted As Showing That Mental Rotation Is Used Tomentioning
confidence: 99%
“…A related study by Corballis and Nagourney (1978) found that when subjects classified misoriented characters as letters or digits there was also only a tiny effect of orientation on decision time. White (1980) had subjects discriminate handedness, category (letter vs digit), or identity for standard or reversed versions of rotated characters. The presentation of each stimulus was preceded by a cue (sometimes inaccurate) about its handedness, category, or identity, in the three judgment tasks, respectively.…”
Section: Evidence Interpreted As Showing That Mental Rotation Is Used Tomentioning
confidence: 99%
“…However, several arguments suggest that this possibility is not quite viable. First, the identification of single letters or letterlike stimuli might be affected little by planar orientation (Corballis & Nagourney, 1978;Corballis, Zbrodoff, Shetzer & Butler, 1978;Eley, 1982;Koriat & Norman, 1989;White, 1980; but see Jolicoeur & Landau, 1984;Jordan & Huntsman, 1995;McMullen & Jolicoeur, 1990). Were that indeed the case, it would be wasteful if the product of single letter identification was not used in the process of reading inverted texts.…”
Section: What the Process Might Bementioning
confidence: 99%